CO2 Adsorption by Modified Palm Shell Activated Carbon (PSAC) Via Chemical and Physical Activation and Metal Impregnation. Issue 11 (1st November 2016) - Younas, Muhammad; Leong, Loong Kong; Mohamed, Abdul Rahman; Sethupathi, Sumathi
Abstract : The aim of this study was to verify the ability of nickel-impregnated palm shell activated carbon (PSAC) for CO2 adsorption and compare its performance with the chemically and physically activated PSAC. Sodium hydroxide and CO2 were used as activating agents for chemical and physical activation, respectively. Nickel nitrate hexahydrate (Ni(NO3 )2 ·6H2 O) was used as a precursor for metal impregnation. The effect of different chemical loadings (NaOH: 20–50 wt%), metal impregnation (Ni(NO3 )2 ·6H2 O: 16–28 wt%), and heat treatment time (1–4 h) was studied as parameters. Adsorption capacity was calculated using breakthrough graphs. The effect of humidity on CO2 adsorption and desorption of CO2 was also investigated in this study. The results revealed that chemically modified PSAC yields the highest adsorption capacity (48.2 mg/g) compared to other methods of activation. Interestingly, it was found that the adsorption capacity of nickel-impregnated PSAC was similar to other types of metal-impregnated activated carbon. Humidity gave a negative effect on CO2 adsorption. In summary, results showed that chemical activation is an efficient technique to modify PSAC for CO2 adsorption.